Women's Movement Model in Used Cooking Oil Alms: Efforts to Build Social Solidarity - Lestari, Soetji; Suyanto, Edy; Widyastuti, Tri Rini (Journal of Ecohumanism, 2024)
The aim of this research is to empower women to participate in the used cooking oil alms movement and to examine the used cooking oil alms movement model. The research method uses descriptive qualitative, the research subjects are women who are members of the Wadas Kelir Berbagi (Wadas Kelir Sharing) Community who were taken using purposive sampling. Data collection used in-depth interviews, observation, focus group discussions (FGD), and secondary data analysis. Data was analyzed using interactive analysis. The results of the research show that women’s understanding of the used cooking oil alms movement is very good. They also really support this movement and their level of participation is high, reflected in their high involvement in this activity so that every month they can collect large amounts of used cooking oil. The model for managing the used cooking oil alms movement is carried out by women and the results are used for social activities for underprivileged groups, such as (a) health assistance for the elderly, (b) basic food assistance, (c) educational assistance for orphans, (d) Friday Blessings activities, (e) assistance for community service work, (f) assistance for tadarusan (reading Quran together), (g) assistance for mosque administrators, (h) giving vegetables to housewives during the Sunday Morning recitation, and other social assistance. It is necessary to socialize the used cooking oil alms movement among women and household assistants outside the Wadas Kelir Sharing Community so that this movement is more widespread.